2019
DOI: 10.1029/2018ef001050
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the Influence of Human‐Induced Climate Change on an Extreme Fire Season

Abstract: A record 1.2 million ha burned in British Columbia, Canada's extreme wildfire season of 2017. Key factors in this unprecedented event were the extreme warm and dry conditions that prevailed at the time, which are also reflected in extreme fire weather and behavior metrics. Using an event attribution method and a large ensemble of regional climate model simulations, we show that the risk factors affecting the event, and the area burned itself, were made substantially greater by anthropogenic climate change. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
120
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(136 citation statements)
references
References 47 publications
3
120
1
Order By: Relevance
“…Abatzoglou and Williams (2016) found that for the western United States human-caused climate change more than halved humidity of forest fuels since the 1970s and doubled the cumulative area of forest fires since 1984. A recent study by Kirchmeier-Young et al, (2018) found a strong influence of climate change on the 2017 British Columbia wildfires, with 50 such events being 2-4 times more likely with climate change in the CanESM2 model. Abatzoglou et al (2018) found that increases in extreme fire weather days due to anthropogenic climate change are evident on 22% of burnable land area globally.…”
Section: Introductionmentioning
confidence: 99%
“…Abatzoglou and Williams (2016) found that for the western United States human-caused climate change more than halved humidity of forest fuels since the 1970s and doubled the cumulative area of forest fires since 1984. A recent study by Kirchmeier-Young et al, (2018) found a strong influence of climate change on the 2017 British Columbia wildfires, with 50 such events being 2-4 times more likely with climate change in the CanESM2 model. Abatzoglou et al (2018) found that increases in extreme fire weather days due to anthropogenic climate change are evident on 22% of burnable land area globally.…”
Section: Introductionmentioning
confidence: 99%
“…In the record‐breaking 2017 extreme wildfire season in British Columbia, Canada, over 1.2 million ha burned. Human impacts of these fires included displacement of over 65,000 people, as well as impacts on human health and air quality . Extreme warmth and dryness are regarded as key contributing factors to wildfires, and July–August were anomalously hotter and dryer that year than any other year in the analyzed record, which began in 1961.…”
Section: Case Studies Of Extreme Events: Environmental Catastrophes Fmentioning
confidence: 99%
“…Extreme warmth and dryness are regarded as key contributing factors to wildfires, and July–August were anomalously hotter and dryer that year than any other year in the analyzed record, which began in 1961. Using a large ensemble of simulations performed with a regional climate model, Kirchmeier‐Young et al . argue that the wildfires were partially attributable to climate change and made substantially more probable in light of anthropogenic warming.…”
Section: Case Studies Of Extreme Events: Environmental Catastrophes Fmentioning
confidence: 99%
See 2 more Smart Citations